Self Control Of Nomophobia During The Covid-19 Pandemic - Setiawan, Lilik; Heni, Sutiyah (Journal of Applied Nursing and Health, 2023)
The Covid-19 pandemic has had an impact on education which is now being carried out online (distance learning with the systemonline) withsmartphone. as a resultsmartphone excessively gives the effect of anxiety or fear when not in contact withsmartphone or so callednomophobia. In anticipation of usesmartphone excess, self-control is needed that is inherent in a person. Research objectives to find outSelf Control ToNomophobia during the Covid-19 Pandemic for Students of the D3 Nursing Study Program STIKES Karya Husada Kediri. Descriptive research design, population of 170 respondents, sample of 63 respondents, techniquepurposive sampling, instrument with a questionnaire sheet, the research was carried out on 1-28 February 2022. The research variable wasSelf Control against Nomophobiaduring the Covid-19 Pandemic. Data were analyzed using a range of values ​​and interpreted quantitatively. The results of the research from 63 respondents showed that the majority of respondents 70% hadself control medium category and almost half of the respondents 30% haveself control the highest. Self control influenced by the factors of residence, duration of smartphone playing and preferred learning techniques as well as gender. It is expected that respondents who haveself control being to improveself control to anticipate usesmartphone excessively by way of usingsmartphone wisely and limit themselves in the use and respondents who haveself control high to maintainself control possessed to limit oneself in the effects of usesmartphone.